2005
DOI: 10.1029/2004gl021827
|View full text |Cite
|
Sign up to set email alerts
|

Rayleigh‐Taylor instability of a particle packed viscous fluid: Implications for a solidifying magma

Abstract: [1] We performed laboratory experiments of RayleighTaylor instability of superposed viscous fluids where the upper layer contains denser spherical solid particles. A series of experiments are made by varying the viscosity and the particle diameter, and we measure the growth rate and the wave length of the instability. The instability consists of fine-scaled plumes, which coalesce as they descend. Plumes are observed to form intermittently and the particle layer thins with time, which finally descend as blobs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 13 publications
4
30
0
Order By: Relevance
“…First is that they both have upward pointing cusps. Similar cusps have been previously observed in RayleighTaylor instability of a liquid-immersed granular medium (e.g., Michioka and Sumita 2005;Shibano et al 2012). In addition, for both cases, the preserved flame structures do not fully penetrate through the upper layer.…”
Section: Comparison With the Sedimentary Rockssupporting
confidence: 86%
“…First is that they both have upward pointing cusps. Similar cusps have been previously observed in RayleighTaylor instability of a liquid-immersed granular medium (e.g., Michioka and Sumita 2005;Shibano et al 2012). In addition, for both cases, the preserved flame structures do not fully penetrate through the upper layer.…”
Section: Comparison With the Sedimentary Rockssupporting
confidence: 86%
“…The unevenness of the lower interface is obviously a gravity-induced instability (Rayleigh-Taylor instability). Some researchers have reported that such an instability occurs at the suspension-fluid boundary even though there is no distinct interface between them [19][20][21][22][23].…”
Section: Settling Behavior Of Stratified Suspensionmentioning
confidence: 99%
“…In a stratified suspension with the positive concentration gradient against the gravity, the interfacial instability occurs at the suspension-fluid boundary and it brings about a lateral variation of the concentration [19][20][21][22][23]. In this case, the suspension behaves as an immiscible fluid even though there is no distinct border with pure fluid.…”
Section: Introductionmentioning
confidence: 99%
“…(9)). Open inverted triangles and open triangles are the equivalent loss modulii calculated from viscosity measurements of the same sample, using a rotating viscometer at shear rates of 0.1 and 1 (1/s), respectively (Michioka, 2005). (For interpretation of the references to color in this figure legend, the reader is referred to the web version of this article.)…”
Section: Structural Irreversibility and Recoverymentioning
confidence: 99%